Balanced Suspension versus Pillow on Preoperative Pain for Proximal Femur Fractures: A Randomized Controlled Trial - Varah Yuenyongviwat; Chonthawat Jiarasrisatien; Khanin Iamthanaporn; Theerawit Hongnaparak; Boonsin Tangtrakulwanich (Advances in Orthopedics)
Introduction. To evaluate the efficacy of a balanced suspension system, using the Thomas splint, with Pearson attachment, compared with a pillow for preoperative pain in patients with proximal femoral fractures. Materials and Methods. Sixty patients with proximal femur fractures were randomized into two groups: a balanced suspension group and a pillow group. In the first group, a balanced suspension was applied after length adjustment, to match the patient’s leg and thigh. In the pillow group, a pillow was placed below the patient’s leg, to position the patient’s hip in a semiflexion and external rotation position. Preoperative pain severity, by using a verbal numerical rating scale (VNRS), the amount of morphine consumed, and complication were recorded. Results. There were no differences in patient characteristics between the groups. The mean VNRS for pain was not statistically different between the groups, from the start of the study up to 48 hours. The mean of morphine consumption was not different between the groups at the start of the study, on day 1, and on day 2 (p=0.25, 0.89, and 0.053, respectively). Conclusions. A balanced suspension did not improve patient outcome to the same level as other tractions in previous studies. Hence, other methods for reducing pain, while waiting for definite operations, should be focused on. The clinical trial is registered with TCTR20150514002.